Pengembangan Soft Skill dalam Pelaksanaan Kampus Mengajar Mahasiswa PAI UNSIQ Jawa Tengah - Syaroni, Wahib; Tafyiroh; Imron, Ali (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
This study originates from the application of the Free Learning Curriculum and Campus Independent Learning, which aims to enhance the soft skills of students in the education profession program. Despite existing literature, there has been a gap in addressing soft skills development specifically in the context of campus teaching. This research focuses on how the Islamic Religious Education (PAI) program works to cultivate students' soft skills during campus teaching. It employs a qualitative descriptive approach, utilizing observation, documentation, archival records, and interviews for data collection. Findings reveal that the PAI program facilitates campus teaching by ensuring effective learning processes and providing students with knowledge through microteaching and Field Experience Practices (PPL). The study took place at the PAI program of UNSIQ in Wonosobo, Indonesia.